2014
DOI: 10.1364/ol.39.001501
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced radiative recombination and suppressed Auger process in semipolar and nonpolar InGaN/GaN quantum wells grown over GaN nanowires

Abstract: The mechanism behind the improved light emission properties of semipolar and nonpolar InGaN/GaN multiple quantum wells (MQWs) conformally grown over n-GaN nanowires (NWs) was studied using variable-temperature photoluminescence and time-resolved photoluminescence (TRPL). A reduced internal polarization electric field was found to account for the observed enhancement in the radiative recombination rate and internal quantum efficiency of the MQWs on NWs. Additionally, the excitation-dependent TRPL results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
7
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
5
7
0
Order By: Relevance
“…The fitted carrier lifetimes (fast component) for samples b and d are 2.19 ns and 8.44 ns, respectively. It was reported that point defects and impurities are the main factors determining emission intensity rather than threading dislocations [22,23,40]. Hence, it reveals that the emission intensity in MQS increases by employing the AlGaN undershell, mainly due to the reduction of point defects density in the MQS active area including the c-, r-, and m-planes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fitted carrier lifetimes (fast component) for samples b and d are 2.19 ns and 8.44 ns, respectively. It was reported that point defects and impurities are the main factors determining emission intensity rather than threading dislocations [22,23,40]. Hence, it reveals that the emission intensity in MQS increases by employing the AlGaN undershell, mainly due to the reduction of point defects density in the MQS active area including the c-, r-, and m-planes.…”
Section: Resultsmentioning
confidence: 99%
“…However, the dislocation defects and triangular defects determine the weaker emissions than that of m-planes. The internal quantum efficiency (IQE) value can be approximately derived by comparing PL intensity at room temperature with respect to that measured at low temperature [40]: IQE(RT) = I(RT)/ I(LT), where I(RT) and I(LT) denote the integrated intensity of PL measured at room temperature (300 K) and low temperature (12 K). Assuming the IQE at 12 K is 100%, the estimated IQE values for samples b and d are 29.32% and 35.52% at room temperature, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Relieved QCSE was hence achieved with an improved overlap of electron−hole wave functions for MQW. Conse− quently, the probability of dipole transition in the semipolar and nonpolar QWs was enhanced for more efficient radia− tive recombination [44]. Strain is directly responsible for the piezoelectric polar− ization.…”
Section: Wave Functions Overlap Improvement Of Electrons and Holesmentioning
confidence: 99%
“…Within the SBMQWs, thicknesses & compositions are selected with the aim which the compressive worry within the wells is modified through the flexible stress within the obstacles. R. Arvind Pawan et al planned a novel highlow indium make up and then prestrained the InGaN/GaN MQW system of environmentally friendly LED [33]. With this MQW the original 4 QWs possess a reduced indium aspect contained InxGa1?…”
Section: Wave Functions Overlap Improvement Of Electrons and Holesmentioning
confidence: 99%